Do Organizational Support and Occupational Stressors Influence Burnout in Teachers? - Baptista, Makilim Nunes; Cardoso, Hugo Ferrari [UNESP] (Instituto Brasileiro de Avaliacao Psicologica (IBAP), 2021)
This study evaluated the relationship between perceived work support, occupational stressors and burnout in a sample of 102 teachers, testing a model based on structural equations. The Labor Support Scale (ESUL), the Workplace Stress Vulnerability Scale (EVENT) and the Brazilian Burnout Scale (EBB) were applied. From the results, the EBB correlated positively and moderately with the EVENT and negatively and with a weak magnitude with the ESUL. The EVENT and ESUL presented a negative and weak correlation. Using the path analysis model, stressors at work mediated the relationship between work support and burnout. The social interaction dimension (ESUL) predicted the climate and organizational functioning (EVENT), which in turn directly impacted emotional exhaustion/professional frustration and depersonalization/detachment (EBB). The study demonstrates the importance of investigating these constructs in the school context, aiming to support the planning of interventions and the reduction of stressors and burnout indicators.
O suporte Laboral e os Estressores Ocupacionais Influenciam o Burnout em Professores?
Keywords: Burnout; Occupational stressors; Organizational support; teachers